Analysis of Attacks and Cybersecurity in the Health Sector During a Pandemic COVID-19: Scoping Review - Awaludin Awaludin; Wahyu Sulistyadi; Alexandra Francesca Chandra (Journal of Social Science, 2023)
COVID-19 as a global pandemic in March 2020 medical personnel and all types of patients with various chronic conditions is undeniably the largest group of users of digital technology during the pandemic. Increased exposure and massive use of the internet is certainly a potential security threat in itself, especially in the threat of cyber-attacks. The purpose of this study is to analyze cyber-attacks and security in the health sector during the COVID 19 pandemic. The scoping review was conducted by searching two main scientific databases (PubMed and Scopus) using the search formula “COVID 19, Pandemic and cyber-attack, cyber security.” Reports, news articles or websites are also included if they are directly related to previously published work, or if they are the only sources available at the time of writing. Only articles in English published in the last decade are included (i.e., 2009-2020) to focus on current problems, challenges, and solutions. In total, 34 papers were included in the review. We found information technology in the health sector that was used during the COVID 19 pandemic. The COVID-19 pandemic situation is a type of non-traditional security that has a broad impact on various aspects of human life, including the health sector. At a time when many countries have responded to the pandemic situation with various restrictive policies to the prohibition of mobilization, people are adapting by shifting to a new landscape of activity. The cyber world is then used by the community to continue to run productivity. This then has implications for the increase in internet users globally, including Indonesia. Some of the cyberattacks include the practice of phishing emails targeting individual and corporate entities, ransomware targeting healthcare facilities and companies. Further research is needed, especially exploring research on cyber-attacks during a pandemic from the point of view of implementation of cyber security.